Analysis on post competence of pediatric physicians of tertiary general hospitals under medical union - Gao, S.; Gao, Y.; Gu, Z; Wang, X.; He, Y.; Gu, W.; Zhang, L.; Ramalho, N.; Jiang, L. (Chinese Journal of Graduate Medical Education, 2018)
Since the medical union have clearly become a regional medical model advocated by the government, various localities begun to build medical union according to the trend of social and economic development and the requirements of regional health planning. Medical resources, hierarchical medical system and residency training models of the medical union have become important research directions. In recent years, the high loss rates in pediatric physicians has caused shortage of supply in pediatric medical service. It is urgent to train new pediatricians to meet the existing needs. By analyzing pediatric physicians’ post competence, this study wishes to explore suitable training models for pediatricians in tertiary general hospitals under medical union. The limitations of the existing training methods of pediatricians were pointed out through the literature review. Meanwhile, combined with the needs and characteristics of the medical union, the teaching models were explored based on post competence in terms of training design and methods. For pediatricians of different sub-professions, the post competency elements should be determine with a variety of research methods. And the post competence oriented education and training work should be constantly adjusted and perfected according to the changes of the environments inside and outside the hospital.